2013
DOI: 10.1002/bio.2515
|View full text |Cite
|
Sign up to set email alerts
|

Spectrofluorimetric analysis of gemifloxacin mesylate in pharmaceutical formulations

Abstract: A simple, rapid and highly sensitive spectrofluorimetric method was developed for determination of gemifloxacin mesylate (GFX) in tablets. The method is based on measuring the native fluorescence of GFX in isopropanol at 400 nm after excitation at 272 nm. The fluorescence-concentration plot was rectilinear over the range of 0.01-0.50 µg/mL with a lower detection limit of 1.19 ng/mL and quantification limit of 3.6 ng/mL. The method was fully validated and successfully applied to the determination of GFX tablets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Satisfactory results were obtained with Al when compared to others. Moreover, the use of cheaper and PVC-insulated Al wire was very widely used in constructing the ionselective electrodes for determining aromatic amines [53], cationic surfactants [54], triarylmethane dyes [55], 4-aminoacetanilide [56], septonex, pilocarpine, ethylmorphine, homatrophine and cinchocaine [57], procaine and trimecaine [58], atrophine [59], cefditoren [60], etc. Therefore, an Al wire was used as medium of conductor in measuring potentials of QTF solutions using both the proposed sensors.…”
Section: Choice Of Conducting Wirementioning
confidence: 99%
“…Satisfactory results were obtained with Al when compared to others. Moreover, the use of cheaper and PVC-insulated Al wire was very widely used in constructing the ionselective electrodes for determining aromatic amines [53], cationic surfactants [54], triarylmethane dyes [55], 4-aminoacetanilide [56], septonex, pilocarpine, ethylmorphine, homatrophine and cinchocaine [57], procaine and trimecaine [58], atrophine [59], cefditoren [60], etc. Therefore, an Al wire was used as medium of conductor in measuring potentials of QTF solutions using both the proposed sensors.…”
Section: Choice Of Conducting Wirementioning
confidence: 99%
“…1). Few analytical methods appeared in the literature for the determination of this drug including spectrophotometric [21][22][23][24], LC [25][26][27], HPLC [28,29], electrophoresis [30,31] and spectrofluorimetry [32,33] were reported for analysis of GFX.…”
Section: Introductionmentioning
confidence: 99%
“…Reviewing the literature revealed that only one high pressure liquid chromatography (HPLC) method has been published concerning the analysis of LE‐300 . Spectrofluorimetry continue to be very popular, because of its simplicity, specificity and low cost . Therefore the aim of the present study is to develop and validate a simple, rapid and sensitive spectrofluorimetric method for the quantitative determination of LE‐300 in mice plasma by using its native fluorescence in methanol.…”
Section: Introductionmentioning
confidence: 99%